Bioenergy beyond the German "Energiewende"–Assessment framework for integrated bioenergy strategies. (November 2020) - Thrän, Daniela; Bauschmann, Martin; Dahmen, Nicolaus; Erlach, Berit; Heinbach, Katharina; Hirschl, Bernd; Hildebrand, Jan; Rau, Irina; Majer, Stefan; Oehmichen, Katja; Schweizer-Ries, Petra; Hennig, Christiane
Abstract: To fulfil the ambitious greenhouse gas reduction targets in Germany requires a fundamental transformation of the energy system. Accordingly, today's bioenergy value chains are faced with substantial transformations to find their role in 2050's low carbon emission energy and supply systems. In this regard, not only economic, environmental, and social aspects need to be taken into consideration. The technology maturity, flexible energy generation and supply and the ability to combine the technologies with CO2 capture are relevant aspects for future bioenergy systems. To evaluate appropriate options for a future energy system an assessment framework with 29 criteria was developed in form of an assessment matrix, and applied for several bioenergy technology pathways. The results show much larger challenges for the implementation and transformation of lignocelluse-based pathways than of biogas-based ones. Trade-offs of the assessment criteria are shown in a heat map. Results might support policy decision makers to develop and implement a long term bioenergy strategy and thus a successful transformation towards a sustainable energy system 2050. Graphical abstract: Image 1 Highlights: Today's bioenergy provision needs transformation to serve renewable energy systems. With 29 criteria several bioenergy transformation pathways are holistically assessed. Results show hot spots, where effort for a successful transformation is necessary. Large bioenergy systems are more suitable for BECCS integration. Small systems tend to show better social performance.